Life-based financial literacy book as a teaching solution in the era of the COVID-19 pandemic - Syahrul Munir; Agung Haryono; Sri Handayani; Yogi Dwi Satrio (University of Merdeka Malang, 2021)
Nowadays, the problem of teachers in Economics is how a teacher should teach not only cognitive abilities but the ability to apply Economics in daily life. This community service program aims to provide skills for Economics teachers in teaching financial literacy to students. The method of implementation in this activity is training and mentoring in the implementation of financial literacy books. This program is intended for Economics/Accounting teachers at MGMP Malang City. This program was carried out in four stages, namely socialization and discussion, implementation of problem-solving, training and mentoring, and evaluation. The implementation of this life-based “financial literacy” book provides insight to teachers about the implementation of financial literacy and learning innovations that can be applied to Economics learning in schools in the future. This activity is a forum for the development of learning innovations in the Economics/Accounting Subject Teacher Community or Musyawarah Guru Mata Pelajaran (MGMP).